Human-carnivore conflict mitigation and lion population viability in Uganda’s Queen Elizabeth National Park - Schwartz, Michael W. (Frontiers in Conservation Science, 2024)
The Uganda Carnivore Program (UCP), located in Queen Elizabeth National Park (QENP), has-among other large carnivore research and conservation measures-engaged in human-carnivore conflict mitigation and prevention efforts since 2015. UCP's experiential lion tourism program funds compensation to local communities for livestock losses to promote carnivore tolerance and conservation. But while UCP's conflict mitigation and prevention trials-through direct payments in response to forensically determined cases of livestock depredation by lion (Panthera leo)-may be aiding in the goal of maintaining lion viability in QENP and the greater Queen Elizabeth Conservation Area (QECA), compensation does not preclude ongoing challenges. These include unsustainable resource uses from human population growth and illegal expansions, subsequent land use changes, illegal livestock grazing and related husbandry practices, and compensation financing shortages. Of note regarding compensation is assessing whether claims of livestock depredation are genuine or not. Nevertheless, disruption to UCP's experiential lion tourism and compensation programs could result in increased retaliatory killings of lions, thus further reducing an already low lion population. As compensation includes the area's large carnivore guild, disruption could also mean further reductions in leopard (Panthera pardus) and spotted hyena (Crocuta crocuta) populations from retaliatory killings. Based on a perspective of UCP's compensation trials and related challenges, several recommendations, including the introduction of compensation percentage rates based on rewards-based frameworks, would strengthen human-carnivore conflict mitigation as part of lion and other large carnivore conservation. This would benefit QENP, greater QECA, and other protected areas where people, livestock, and large carnivores share space.